2019
DOI: 10.1021/acs.analchem.9b02096
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Immobilization of Single-Domain Antibodies Using SpyTag/SpyCatcher Yields Improved Limits of Detection

Abstract: Single-domain antibodies (sdAb), recombinantly produced variable heavy domains derived from the unconventional heavy chain antibodies found in camelids, provide stable, well-expressed binding elements with excellent affinity that can be tailored for specific applications through protein engineering. Complex matrices, such as plasma and serum, can dramatically reduce assay sensitivity. Thus, to achieve highly sensitive detection in complex matrices a highly efficient assay is essential. We produced sdAb as gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 46 publications
0
54
0
Order By: Relevance
“…The 13 aa SpyTag with a short linker is chemically synthesized on the agarose, while the POI fused with SpyCatcher and intein Mtu ΔI-CM (H73V/T430S) is captured by the SpyTag-modified resin, followed by the self-cleavage of the intein to release the POI. PDB, Protein Data Bank [Color figure can be viewed at wileyonlinelibrary.com] component in conjunction with glutathione S-transferase (GST) for immobilization of proteins on magnetic microspheres and nanoparticles for detection (Anderson et al, 2019;Ma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The 13 aa SpyTag with a short linker is chemically synthesized on the agarose, while the POI fused with SpyCatcher and intein Mtu ΔI-CM (H73V/T430S) is captured by the SpyTag-modified resin, followed by the self-cleavage of the intein to release the POI. PDB, Protein Data Bank [Color figure can be viewed at wileyonlinelibrary.com] component in conjunction with glutathione S-transferase (GST) for immobilization of proteins on magnetic microspheres and nanoparticles for detection (Anderson et al, 2019;Ma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that surface-coated SpyCatcher1 can be used as a capture reagent for in vitro assays 17,27 ( Figure 4A). We wanted to establish such an oriented immobilization with the faster-reacting SpyTag2 and SpyCatcher3, which should provide an advantage at the low protein concentrations used for immobilization in ELISA assays.…”
Section: Assay Performancementioning
confidence: 99%
“…Nevertheless, there is a small number of studies in which periplasmic expression of SpyTagged proteins were described 16,17,18 . Interestingly, during our initial investigation, we also discovered one antibody which could be produced in our standard E. coli expression strain, albeit with low yields.…”
Section: Spytagged Antibody Fragments Have Been Expressed In E Coli mentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to conventional IgGs (150 kDa), the tiny dimension of nanobody confers the exclusive capacity to bind to cryptic epitopes of viruses [2], a characteristic that at the present could be particularly useful to produce reagents suitable for coronavirus studies. Over the years, it emerged that VHHs are effective crystallography chaperones and molecular tools for protein structural characterization [3][4][5], convenient carriers for radioisotopes with extremely short half-life to use for in vivo PET/ SPECT imaging [6][7][8][9][10], valid immunoreagents for the controlled and oriented functionalization of nanoparticles, nanogels and biosensors [11][12][13][14] and that they can be even internalized by mammalian cells when provided with a suitable leader peptide [15]. More recently, their minimal dimension has been particularly appreciated by scientists looking for binders suitable to optimize the performance of super resolution microscopy [16][17][18] and to create tandem chimeric antigen receptors (CARs) that show higher target specificity due to the possibility of binding simultaneously multiple antigens [19].…”
Section: Introductionmentioning
confidence: 99%